Теоретические основы маркетингового управления деятельностью предприятия: социальный аспект - Усеинова, Л. (Культура народов Причерноморья, 2014)
В данной статье рассмотрен социальный аспект маркетингового управления деятельностью
предприятия в современных условиях, цели системы маркетинга, определены основные подходы, на основе
которых коммерческие организации ведут свою маркетинговую деятельность. У даній статті розглянуто соціальний аспект маркетингового управління діяльністю
підприємства у сучасних умовах, цілі системи маркетингу, визначені основні підходи, на основі яких
комерційні організації ведуть свою маркетингову діяльність. Practical Application of marketing has shown that the use of only the individual components, such as the
study of the goods, works or services and market forecasting, does not give the desired effect. Only a holistic approach
can effectively break into the market with goods and services. This article discusses the social aspect of marketing
management activities of the enterprise in modern conditions, the purpose of marketing, the basic approaches on which
commercial organizations conduct their marketing activities. Highlighting the objectives of the marketing system:
attain the highest consumption, maximizing consumer satisfaction, providing the widest selection, maximizing quality
of life. The basic elements of marketing: market conditions and dynamics of the demand for these tourist and hotel
services; changes in prices for travel and accommodation services and their substitutes; forecast revenue growth of
consumers and their needs for these services; promotion of tourist services; Planning the range of goods and services.
Defined the special role of the knowledge base and range of information services provided by tourism enterprises in the
reinforcement of the tourist product, as well as consider a system of customer behavior from the perspective of the
object of competition.